Conceptualising the emancipatory potential of populism: A typology and analysis. (April 2023) - Beresford, Alexander; Beardsworth, Nicole; Findlay, Kyle; Alger, Simon
Abstract: A central claim common to all populist movements is that they are committed to giving voice and power to those who have been forgotten, maligned, or marginalised by the status quo. However, consensus holds that they rarely – if ever –fulfil this commitment. And yet, there is a gap in our understanding of why. This article provides an original conceptual distinction between vanguardist and devolutionary populism. While the former is concerned with accessing and wielding power within the existing spaces of politics, the latter is concerned with provoking and enabling popular reimaginings of the very spaces in which politics is constituted. Using the case of South Africa, we demonstrate how our novel method can help determine where a movement might sit on the continuum between vanguardist and devolutionary populism. We make a populist campaign legible by combining detailed archival work to understand the movement's background with cutting edge cartographic techniques to map its spread and reception in digital spaces. Our conceptual distinction and methods create space to consider whether, and in what circumstances, populists might reinvigorate politics or, alternatively, compound the cynicism, divisions and tensions manifest within contemporary global politics.